Advanced observation of brain and nerve cells using two-photon microscopy with novel techniques. (21st September 2022) - Ishii, Hirokazu; Takahashi, Taiga; Yamaguchi, Kazushi; Nemoto, Tomomi
Abstract: Two-photon excitation fluorescence microscopy [two-photon microscopy (2PM)] is a robust technique for understanding physiological phenomena from the cellular to tissue level, attributable to the nonlinear excitation process induced by near-infrared ultrashort laser light pulses. Recently, we have been promoting the use of semiconductor lasers, adaptive optics, vector beams and nanomaterials to improve the observation depth or spatial resolution. The developed semiconductor-based laser light source successfully visualized the structure of the enhanced yellow fluorescent protein (EYFP)-expressing neurons at the hippocampal dentate gyrus without resecting the neocortex and neuronal activity in the hippocampal cornu ammonis (CA1) region in anesthetized mice at video rates. We also proposed using fluoropolymer nanosheets of 100-nm thickness for in vivo imaging and realized a wide field of view during anesthetized mouse brain imaging of 1-mm depth. Furthermore, the developed adaptive optical 2PM visualized single dendritic spines of EYFP-expressing neurons in cortical layer V of the secondary motor cortex, which had been difficult to observe due to the curvature of the brain surface. In addition, we combined 2PM and stimulated emission depletion microscopy to improve spatial resolution. This combined microscopy is noninvasive and has a superior spatial resolution, exceeding the diffraction limit of the conventional light. In this review, we describe our recent results and discuss the future of 2PM.